2023
DOI: 10.1038/s41565-023-01329-y
|View full text |Cite
|
Sign up to set email alerts
|

Oligomer nanoparticle release from polylactic acid plastics catalysed by gut enzymes triggers acute inflammation

Abstract: Although the risks of microplastics in environmental exposure and human health are being increasingly studied, little is known about the behavior of "eco-friendly" bioplastics in humans, especially their effects on our gastrointestinal tract. Here we demonstrate that enzymatic hydrolysis of bio-based polylactic acid (PLA) microplastics rapidly generates an excess of nanoplastic particles by competing for triglyceridedegrading lipase during gastrointestinal processes. These tiny nanoparticles are oligomers form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 50 publications
1
54
0
Order By: Relevance
“…Nanoplastics and MPs with small particle sizes can even enter cells, directly interfering with intracellular lipid synthesis, transport, and metabolic homeostasis . Besides, the toxic oligomers released by PLA-MPs in the body were another vital factor for exacerbating the abnormalities of the digestive system and lipid metabolism in the body . Therefore, compared with conventional nondegradable MPs, PLA-MPs have the property that they can be partially degraded in the body, which will produce a large number of nanoparticles and toxic polymers, which will further enhance their toxicity in vivo. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoplastics and MPs with small particle sizes can even enter cells, directly interfering with intracellular lipid synthesis, transport, and metabolic homeostasis . Besides, the toxic oligomers released by PLA-MPs in the body were another vital factor for exacerbating the abnormalities of the digestive system and lipid metabolism in the body . Therefore, compared with conventional nondegradable MPs, PLA-MPs have the property that they can be partially degraded in the body, which will produce a large number of nanoparticles and toxic polymers, which will further enhance their toxicity in vivo. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…58 Besides, the toxic oligomers released by PLA-MPs in the body were another vital factor for exacerbating the abnormalities of the digestive system and lipid metabolism in the body. 59 Therefore, compared with conventional nondegradable MPs, PLA-MPs have the property that they can be partially degraded in the body, which will produce a large number of nanoparticles and toxic polymers, which will further enhance their toxicity in vivo. 59,60 PLAH Exposure Altered the Diversity and Composition of Fecal Microbiota.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Moreover, the distinct consequence of high doses and positively charged NPs on soil microbial community structure were clearer at the family level, wherein families with significantly higher relative abundance in PS‐N 3 treatment in NPs group was 1.8 and 2.7 times of that in PS‐N 0.3 and PS‐S 3 treatment, respectively (Figure 1d). Generally, small size plastic contaminants are widely perceived to exert their impacts on microorganisms in a dose‐dependent manner (Liu et al, 2021; Liu et al, 2023; Wang, Li, et al, 2023). Our observations indicate that the alterations of NPs on microbial communities were motivated by high doses and the positive surface charge of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing plastic pollution is undoubtedly becoming a global problem (Borrelle et al, 2020; Stegmann et al, 2022). Owing to the poor management of plastic waste, the large plastic debris can be fragmented into microplastics (0.1 μm–5 mm) and nanoplastics (<0.1 μm) under the actions of mechanical abrasion, thermal/photo‐degradation, and biological degradation (Schiferle et al, 2023; Wang, Li, et al, 2023). Therefore, it is not surprising that microplastics (MPs) and nanoplastics (NPs) are detected in both urban and remote locations (Allen et al, 2022; Machado et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only sporadic studies have revealed the toxic effects of oligomers and monomers generated by BPs on organisms. In a mouse model, polylactic acid (PLA) nanoparticle oligomers were formed during gastrointestinal processes and bioaccumulated in the liver, intestine, and brain, causing intestinal damage and acute inflammation . Polycaprolactone (PCL) oligomers generated by hydrolysis inhibited the growth activity and nitrogen fixation of two cyanobacterial species .…”
Section: Toxic Effects Of Oligomers and Monomersmentioning
confidence: 99%